Modelling and analysing of a 275 kV HVAC transmission line for power system transient studies - Ab Kadir, Mohd Zainal Abidin; Jay, C. Y. (EuroJournals Publishing, 2008)
This paper presents the modelling and analyzing of a 275 kV high voltage AC HVAC) transmission line by using PSCAD/EMTDC software. The study is done based on a real 275 kV transmission line which connected from Kampung Awah - Paka, Terengganu. Pi-section model is presented using the parameters obtained from the calculation and is modelled using PSCAD/EMTDC software. The investigation is carried out to determine the efficiency of the transmission line via the concept of travelling wave. The results of performance of the transmission line are then compared and analyzed with the frequency dependent model and these validation results are really useful especially through experimental studies which are based on the Pi-section model.